Online teaching methodology in the speciality of sanitary area of the master’s degree in teacher training at UNIR, the University on the Internet. - Criado Martín, Antonio J.; Criado Martín, Alejandro; Lanagrán Valero, Eva María; Álvarez-Domínguez, Carmen; Nestares, Eva María; Pérez Largacha, Antonio (CEUR workshop proceedings, 2021)
This paper develops the teaching method that is carried out in the subject of Complements for disciplinary training of health area, belonging to the speciality of health area, in the University Master’s Degree in Teacher for Compulsory Secondary Education, Upper Secondary Education, Vocational Training and Language Teaching, which is taught at the Faculty of Education of the International University of La Rioja, the University on the Internet. This speciality is aimed at training future teachers who will teach in the vocational training cycles of the healthcare area, a teaching with the aim of job placement, being shorter than university degrees. Most of the students' specialities are medicine, nursing, physiotherapy, veterinary medicine, nutrition, dentistry, optometry, etc. The didactic model, with which the subject is conceived, puts the student at the center of the teaching-learning process through active, practical and collaborative work, always online. © 2021 Copyright for this paper by its authors. Use permitted under Creative Commons License Attribution 4.0 International (CC BY 4.0).
Keywords: active methodologies; complements formation discipline; online distance learning; process health; vocational training; Scopus(2)